Reflective Thinking and English-Speaking Ability of Freshmen Education Students - Flores, Brando P.; Reyes, Dexter A.; Cameros, Lemor D.; Andriano , Bea C. Andriano; Dacalanio, Mark Aaron A. (CV. Tripe Konsultan, 2025)
This study aimed to explore the levels of reflective thinking and English-speaking ability among 109 freshmen education students at a private college institution in Davao del Sur, Philippines, and to examine the relationship between these two variables. It used a quantitative descriptive-correlational research design and applied a stratified random sampling technique in gathering data. Findings revealed that the level of reflective thinking among freshmen education students was high, while their English-speaking ability was moderate. Additionally, the relationship between reflective thinking and English-speaking ability was found insignificant and non-correlational, suggesting that other factors might more significantly influence English-speaking skills. These findings indicated the need for targeted interventions to enhance English-speaking abilities alongside promoting reflective thinking practices. Educational administrators and teachers may focus on improving language teaching pedagogies and in creating supportive learning environments that foster these skills. Future research may explore these dynamics to better understand and support student development.